Molecular pathological profiling of selected tumors of the central nervous system using the MLPA method - Dolinová, Iva; Tvrzníková, Eliška; Janoušková, Veronika; Vícha, Aleš; Krsková, Lenka; Jirásek, Tomáš (Ceskoslovenska patologie, 2022)
The current progress and increasing knowledge about the genetic causes of cancer opens up new possibilities for its treatment. However, it is necessary to combine the results obtained using classical pathological methods with sensitive, multiplex molecular pathological methods. The method that meets the required criteria is MLPA based on multiplex PCR reaction. This method detects both changes in gene copy number and DNA methylation and, last but not least, point mutations. The MLPA reaction is applicable to even highly fragmented DNA. At the same time, it is a robust method that can be performed on standard thermocyclers, the fluorescent tip label requires automatic sequencers. Up to 50 genetic markers can be tested in one reaction, a number that allows a diagnostic and prognostic conclusion. All these features lead to the routine use of MLPA analysis not only in diagnosis but also in cancer research. The present article aims to summarize the different types of MLPA reactions, its benefits, but also the potential pitfalls.
Keywords: DNA Methylation; Central Nervous System Neoplasms; Genetic Markers; PCR; nádory centrálního nervového systému; Molecular pathology; Tumors of the central nervous system; genová dávka; Humans; metylace DNA; genetické markery; Gene Dosage; DNA; lidé; MLPA